Training module on the WTO Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS) - Correa, Carlos...[et al.] (UN New YorkUS, 2010)
Seeks to inform trade experts and negotiators of developing countries about key aspects relating to intellectual property rights and more specifically the WTO Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS).